UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% DAUN MIMBA (Azadirachta indica A. Juss. ) DENGAN METODE EKSTRAKSI PERKOLASI TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Yanu Andhiarto; Rina Andayani; Nur Hidayatul Ilmiyah (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
Skin infections most often found in developing countries, especially in the tropics, are purulent skin inflammation (pyoderma), the main cause of Staphylococcus aureus. The increasing number of cases of bacteria that are resistant to antibacterial can encourage the extraction of sources of antibacterial drugs from natural ingredients. One of the plants that is thought to have the antibacterial activity of Staphylococcus aureus is the Neem plant. In this study an antibacterial activity test was carried out with the well diffusion method from 96% ethanol extract of Mimba leaves extracted by percolation method. Phytochemical screening tests obtained 96% ethanol extract of Mimba leaves containing alcaloid, saponins, tannins, steroids / terpenoids and flavonoids. The results of the study on the antibacterial activity test showed a concentration of 75% ethanol extract of 96% Mimba leaves classified as having strong activity, at a concentration of 50% and 25% classified as having moderate activity. It concluded that the three concentrations of 96% ethanol extract of Mimba leaves were able to inhibit the growth of Staphylococcus aureus bacteria.